2015
DOI: 10.1186/s12913-015-1247-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Participatory Learning & Action research to access and engage with ‘hard to reach’ migrants in primary healthcare research

Abstract: BackgroundCommunication problems occur in general practice consultations when migrants and general practitioners do not share a common language and culture. Migrants’ perspectives have rarely been included in the development of guidelines designed to ameliorate this. Considered ‘hard-to-reach’ on the basis of inaccessibility, language discordance and cultural difference, migrants have been consistently excluded from participation in primary healthcare research. The purpose of this qualitative study was to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 45 publications
2
121
0
2
Order By: Relevance
“…Given that public health actions and effects often do not follow a linear time period and may require long periods of time (28, 29, 93), Rutter and colleagues emphasize the importance of tracking proximal, intermediate, and distal processes and outcomes, as well as the importance of modifying approaches in responses to changes in systems (31). The growing field of participatory learning and action (97, 98)—which includes visual and group-based inquiry methods for exploring the process of a given intervention (99, 100)—holds specific relevance for engaging populations in co-learning around implementation and evaluation of health promoting interweaving approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Given that public health actions and effects often do not follow a linear time period and may require long periods of time (28, 29, 93), Rutter and colleagues emphasize the importance of tracking proximal, intermediate, and distal processes and outcomes, as well as the importance of modifying approaches in responses to changes in systems (31). The growing field of participatory learning and action (97, 98)—which includes visual and group-based inquiry methods for exploring the process of a given intervention (99, 100)—holds specific relevance for engaging populations in co-learning around implementation and evaluation of health promoting interweaving approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication must be built in the framework of listening to them in an active way and posing questions by using the appropriate verbal and non-verbal communication skills [19].An initial step the PHC professionals may try to gain a better understanding and feeling of what these people have experienced and require, i.e., "getting into refugees shoes" is by specifically seeking their input asking them about their physical and emotional needs as well as their preferences of receiving health services. To successfully overcome language barriers, the PHC professional ought to consider the socio-cultural beliefs of the patient, as well as to overcome linguistic challenges [6,12]. Here, an appropriate supporting network is needed for the PHC team, facilitating access to interpreting and cultural mediation services.…”
Section: Highlights From the Ecm: The Need For Compassionate Carementioning
confidence: 99%
“…The literature search and interviews with experts found that in order to provide compassionate care crucial problems and barriers occur at the levels of professional, patient, and organisation. Many studies identified the training of professionals in culturally sensitive aspects of care as a core enabler or a critical element of improvement interventions [6,[12][13][14][15].…”
Section: Highlights From the Ecm: The Need For Compassionate Carementioning
confidence: 99%
See 1 more Smart Citation
“…Research methods specifically aimed at engaging patients from underserved groups exist 2. Furthermore, patients or representatives can help to think about which research questions are important to their communities and help prioritise a research agenda.…”
mentioning
confidence: 99%